Answer:
x = -0.24 or 3.73
Step-by-step explanation:
[tex]\frac{-b + \sqrt{b^{2} -4ac } }{2a}[/tex] (There's supposed to be a ± between '-b' and the square root)
[tex]x^{2}[/tex] + 4x + 1 ( [tex]ax^{2} + bx + c[/tex] )
a = -1 ( there's no number before [tex]x^{2}[/tex] so its 1 )
b = 4
c = 1
Substitute into the quadratic equation.
[tex]\frac{-4 + \sqrt{4^{2} -4x1x-1 } }{2x-1}[/tex] ( the [tex]x[/tex] is just the multiplication sign )
= [tex]\frac{-4 + \sqrt{{16} +4 } }{-2}[/tex]
[tex]\frac{-4 + \sqrt{{20} } }{-2}[/tex] = -0.24 [OR] [tex]\frac{-4 - \sqrt{{20} } }{-2}[/tex] = 3.73
( The answers are to 2 decimal places )